What FiveThirtyEight Can Teach Us about Solving the Replication Crisis. Issue 5 (30th December 2022) - Holman, Bennett
Abstract: Numerous philosophers of science have argued that the incentive structure of science is a major contributor to the replication crisis. In this article I review FiveThirtyEight's election forecasting model and show that it confronts similar problems in political polling and successfully mitigates them, not by changing the incentives, but by weighting a pollster's effect on the model by their past reliability. I argue that a similar weighting procedure holds a promising approach to addressing the replication crisis in science.